More Time with Tremor: The Experience of Essential Tremor Versus Parkinson's Disease Patients - Louis, Elan D. (Mov Disord Clin Pract, 2015)
BACKGROUND: A broad range of tremors occur in patients with essential tremor (ET) and Parkinson's disease (PD); despite this, there are virtually no published data that focus on the patient perspective. The aims were to (1) assess the subjective experience of tremor, comparing ET and PD patients and (2) assess the clinical correlates of that experience (i.e., what specific clinical characteristics were associated with more experienced tremor)? METHODS: One hundred twenty‐one ET and 100 PD cases enrolled in a cross‐sectional, clinical‐epidemiological study underwent a detailed clinical assessment, which included a series of standardized questionnaires and neurological examination. The question, “On a typical day, how many waking hours do you have tremor in any body part?” was also administered. RESULTS: Essential tremor cases reported more than 3 times the median number of waking hours experiencing tremor than PD cases: 10.1 ± 7.8 (median, 10.0) versus 5.5 ± 6.3 (median, 3.0) hours (P < 0.001). A small number of cases (especially ET) reported spending ≥16 h/day shaking. Greater number of hours experiencing tremor was associated with female gender, higher Center for Epidemiological Studies Depression Scale scores, greater perceived disability, and, in ET, higher Essential Tremor Embarrassment Assessment scores. CONCLUSIONS: ET patients reported more than 3 times the median number of waking hours experiencing tremor than PD patients. Certain clinical characteristics tracked with more reported tremor, and the number of such hours had clear clinical ramifications—greater number of hours was associated with both psychosocial and functional consequences.